Development of Gas Leakage Detector Using GSM for Factory Safety - Muhamad Tarmizi Sidi Ahmad; Syed Mohammed Uddin; Mohd Izhar A Bakar (Journal of Engineering Technology, 2022)
Nowadays a lot of news that plants exploding occur and because of that a lot of people die, to overcome this problem an idea arises to build a safety system which is a Gas Leakage Detector with GSM for factory safety, this system will detect the gas leakage in a factory environment. if have is any gas leak in that factory it will give an alert by triggering the alarm to notify the worker, it also gives the notification using GSM to the authority which is the authority’s factory that can take some action to avoid unwanted scene happening. With this system, it can prevent from any explosion happening cause of the gas leak. With the addition of GSM in this system, it will improve the safety of the factory because it will immediately call the person in charge.